Social and economic factors influencing intrahousehold food allocation and egg consumption of children in Kaduna State, Nigeria - Lauren S. Blum; Haley Swartz; Gloria Olisenekwu; Irowa Erhabor; Wendy Gonzalez (Maternal and Child Nutrition, 2023)
Abstract Adequate intake of high‐quality nutritious foods during infancy and early childhood is critical to achieving optimal growth, cognitive and behavioural development, and economic productivity later in life. Integrating high‐quality and nutrient‐dense animal source foods (ASFs), a major source of protein and micronutrients, into children's diets is increasingly considered essential to reducing the global burden of malnutrition in low‐ and middle‐income countries. While eggs are an ASF that shows promise for mitigating child undernutrition, interventions promoting egg consumption among children have had mixed results in improving egg intake and child growth outcomes. As part of an evaluation of a demand creation campaign promoting egg consumption, qualitative research was carried out in September 2019 to assess sociocultural and household factors affecting egg intake among young children living in Kaduna State, Nigeria, where a thriving egg industry and childhood stunting rates of 50% exist. Methods included freelisting exercises (11), key informant interviews (11), in‐depth interviews (25) and FGDs (4). Results illuminated cultural rules that restrict egg consumption among children living in low‐income households. These rules and norms reflect social and economic valuations that foster male dominance in household decision‐making and guide food purchasing and intrahousehold food allocation that allow men to consume eggs more regularly. Study results highlight sociocultural considerations when selecting food interventions to address child malnutrition in low‐income contexts. Interventions encouraging increased consumption of ASFs, and specifically eggs in young children, should be informed by formative research to understand sociocultural norms and beliefs guiding egg consumption.